Lindenmeyer systems and the harmony of fractals - Pestana, Pedro (2021)
An interactive musical application is developed for realtime improvisation with a machine based on Lindenmeyer-systems. This has been used on an installation whose goal is to draw the attention of unexperienced users to the wealth of realtime applications in computer music. Issues on human computer interaction and improvisation grammars had to be dealt with, as well as probabilistic strategies for musical variation. The choice of L-systems as a basis for machine composition is a consequence of their ability to create results that easily have aesthetic appeal, both in the realms of sound and image.